Desequilibrando o insucesso: uma proposta de intervenção pedagógica e psicopedagógica na perspectiva piagetiana - Dalevedo, Melissa Cristina de Souza [UNESP]; Camargo, Mayra Laís Marin [UNESP]; Saravali, Eliane Giachetto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays is visible the growing characterization of children as having learning difficulties from the beginning of their school life; any cases that represent a kind of "failure", or, in other words, any case in which the person does not reach the existing expectations to a certain level, this person are already labeled as having learning difficulties, with a serious aggravating factor: it's said that the failure is a student’s fault. In the other side of this perspective, this paper discusses the university extension project "Educational and Psychopedagogical Intervention: contributions for child development," which is aimed at providing fruitful environment for the development of the individual, promoting interventions and appropriate pedagogical and psycho requests in order to help fill in the gaps that may exist and encourage the development of the subject sent to the project. Based on Piaget's theory, the project activities, with respect to diagnostic and intervention procedures, are guided in the balancing process, the environment requests and foundations of learning and operative pedagogy. The project is funded by the University Pro-rectory of Extension, and it takes place at CEES – (portuguese initials for “Education and Health Study Center”), in the Campus II of the Universidade Estadual Paulista Julio de Mesquita Filho - UNESP, Marilia - SP, and has achieved good results.

Atualmente, é visível a crescente caracterização de crianças como tendo dificuldades de aprendizagem, desde o início de sua vida escolar; quaisquer casos que representem uma espécie de “insucesso”, ou seja, quaisquer casos em que o indivíduo não corresponda às expectativas existentes para determinado nível, já são prontamente taxados como dificuldades de aprendizagem, com um sério agravante: a culpabilização do educando por seu insucesso escolar. Em oposição a essa perspectiva, o presente trabalho discorre sobre o projeto de extensão universitária "Intervenção Pedagógica e Psicopedagógica: contribuições para o desenvolvimento infantil", o qual tem por meta oferecer ambiente profícuo ao desenvolvimento do indivíduo, promovendo intervenções e solicitações pedagógicas e psicopedagógicas adequadas com a finalidade de auxiliar a preencher as lacunas que possam existir e estimular o desenvolvimento do sujeito encaminhado ao projeto. Embasadas na teoria piagetiana, as atividades do projeto, no que se refere aos processos de diagnóstico e intervenção, são pautadas nos processos de equilibração, solicitação do meio e fundamentos da aprendizagem e pedagogia operatória. O projeto é financiado pela Pró-Reitoria de Extensão Universitária, realizado no CEES - Centro de Estudos de Educação e da Saúda, Campus II da Universidade Estadual Paulista Júlio de Mesqui Filho - UNESP, Campus de Marília - SP, e tem alcançado bons resultados.
Keywords: Piaget's theory; Learning difficulties; Educational and psychopedagogical intervention; Teoria piagetiana; Dificuldades de aprendizagem; Intervenção pedagógica e psicopedagógica